2014
DOI: 10.3109/07420528.2014.979940
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term microgravity exposure in space on circadian rhythms of heart rate variability

Abstract: We evaluated their circadian rhythms using data from electrocardiographic records and examined the change in circadian period related to normal RR intervals for astronauts who completed a long-term (≥6-month) mission in space. The examinees were seven astronauts, 5 men and 2 women, from 2009 to 2010. Their mean±SD age was 52.0±4.2 years (47-59 yr). Each stayed in space for more than 160 days; their average length of stay was 172.6±14.6 days (163-199 days).We conducted 24-hr Holter electrocardiography before la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…Some neuropeptides can have more prominent ultradian (with a frequency higher than one cycle per day; e.g., 8-hour periodicity) than circadian changes [24]. We previously showed that the circadian rhythm persisted in space in HR and β [9, 12]. Herein, we confirm the presence in space of 24-, 12-, and 8-hour components in several HRV endpoints by the fit of a model including 4 anticipated components.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Some neuropeptides can have more prominent ultradian (with a frequency higher than one cycle per day; e.g., 8-hour periodicity) than circadian changes [24]. We previously showed that the circadian rhythm persisted in space in HR and β [9, 12]. Herein, we confirm the presence in space of 24-, 12-, and 8-hour components in several HRV endpoints by the fit of a model including 4 anticipated components.…”
Section: Discussionsupporting
confidence: 79%
“…Spaceflight dramatically alters cardiovascular dynamics, as illustrated by changes in HRV [12] and a less negative slope β of the fractal scaling [9] confirmed herein. Kleitman's about 90-min BRAC [20] was found to be amplified about 3-fold in space, notably among astronauts of Group 1, in keeping with a corresponding increase in ULF01/TF (0.0001–0.0003 Hz, i.e., 55–166 min) and corresponding decreases in ULF02/TF and ULF03/TF.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Twenty-four-hour ECGs of astronauts were also analyzed to understand the space environment's effect on biological rhythm and cardiac autonomic nervous activity leading to recommendations for maintaining a well-balanced biological rhythm on Earth. One of these recommendations is maintenance of a regular sleep schedule [20]. In studying the sleep patterns of cosmonauts using a miniature device that fits in their pocket [ Figure 8], information is recorded and sent to Earth for analysis of sleep quality.…”
Section: Ii6 Heart Health and Biorhythmsmentioning
confidence: 99%